Co-inoculação de Azospirillum brasilense e uso de gesso na amenização dos efeitos de deficiência hídrica e acidez no subsolo em soja. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Most Brazilian soils present unfavorable chemical conditions for deep root growth due to low levels of calcium (Ca) and toxic levels of aluminum (Al) in the subsoil. Climate change and global warming have caused increasingly intense droughts. This study was carried out to evaluate the influence of co-inoculation of Azospirillum brasilense and the application of agricultural gypsum in mitigating the effects of water deficit and subsoil acidity in soybean plants. The experiment was established as randomized complete blocks design, in a 3 × 2 × 2 factorial scheme, with three replications. The factors studied were: without co-inoculation, with co-inoculation of A. brasilense (AbV5 and AbV6) and with co-inoculation of A. brasilense (AbV5 and AbV6) + application of N-urea at sowing (25 kg N ha -1); without and with gypsum application; and without and with water limitation. At 50 days after emergence, approximately at the R2 developmental stage of soybean, the net photosynthesis rate, stomatal conductance, intracellular carbon concentration, and leaf transpiration were measured using the IRGA meter. Chlorophyll a and b contents were evaluated using the ClorofiLOG chlorophyll meter. Shoot dry mass was measured and the nutrient extraction by shoots was determined. After the plants were removed, the soil columns were sectioned into the 0–10, 10–20, and 20–50 cm layers and a subsample of soil from each layer was collected for chemical analyses. The sectioned soil columns were washed in running water and the dry mass of the roots as well as the number and dry mass of nodules were evaluated. The results showed that the co-inoculation of soybean seeds with A. brasilense did not cause evident benefits in soybean development, regardless of the conditions of water deficiency and acidity in the subsoil. Greater benefits were obtained when the co-inoculation of A. brasilense was associated with the application of N-urea at sowing, especially for Ca uptake and soybean nodulation. Co-inoculation of A. brasilense associated with the use of gypsum did not increase soybean root growth in order to minimize the negative effects of subsoil acidity, regardless of the water condition during plant development. Gypsum application increased Ca and S- SO42- levels in the soil profile, reduced subsoil Al saturation, improved root distribution in the soil profile, and increased Ca uptake and net photosynthesis in the soybean plant. Water stress reduced stomatal conductance (8 to 10%), root dry mass (16%), N uptake (26%), P (15%), K (14%), Ca (21%), and Mg (17%), the number (31%) and the dry mass (28%) of nodules, and the production of soybean shoot dry mass (25%). Considering the damage caused by water stress on soybean development, soil management practices that mitigate the effects of water deficiency should be encouraged.
Keywords: Glycine max; bactérias promotoras do crescimento de plantas; nitrogênio; fosfogesso; Glycine max; plant growth-promoting bacteria; nitrogen; phosphogypsum; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA